Probabilistic Testing and the Evaluation of Student Performance. - Neyhart, Charles A.; Abrassart, A. Eugene (The Accounting Review, 1977)
Abstract ABSTRACT: This paper reports on the technique of Probabilistically Answered Examinations (PAE) as applied to objective tests. The purpose is to establish the relevance of PAE in measuring student performance. A substantive, rather than normative, viewpoint is superimposed, that is, probability assessments are evaluated exclusively within the subject-matter domain in which they are made. After reviewing concepts underlying PAE, it is demonstrated that the methodology is likely to provide more complete information about test scores and the traits measured by the test than that provided by conventional procedures. Examples of performance measures and how they may be applied to PAE are provided.